Damage characteristics of ship structures subjected to shockwaves of underwater contact explosions. (1st May 2016) - Ming, F.R.; Zhang, A.M.; Xue, Y.Z.; Wang, S.P.
Abstract: The damage process of ship structures subjected to underwater contact explosions is characterized by strong nonlinearity, thus there are great challenges in solving such problems. Firstly, the full Smoothed Particle Hydrodynamics (SPH) method for the fluid and structure interaction (FSI) is established based on compressible SPH fluid dynamics and SPH shell. Furthermore, the normal flux method is introduced to treat the interface. However, given the immaturity of the SPH shell in dealing with the fracture of complex structures, an SPH-FEM (Finite Element Method) coupling method for FSI is proposed with the "glue" treatment applied at the interface. The above two methods are verified by an underwater contact explosion experiment. Afterwards, the pressure-time relationship within six charge radii is fitted based on the axisymmetric SPH simulation. On this basis, the flat plates subjected to underwater contact explosions are studied in detail with the application of a combined damage variable. Three stages in the damage process, namely localized bulging, discing and petaling, are observed, and the crack and deflection are found to be sensitive to the changes of peak pressure and impulse respectively. Finally, complex models of a stiffened plate and a ship are established to further study the damage characteristics. Highlights: The full SPH method is applied in underwater contact explosions. The SPH-FEM coupling method for underwater contact explosions is established. The shockwave pressure within six charge radii is fitted. The combined damage variable is used to study the damage characteristics of ship structures.